A novel model for evaluating environmental governance performance based on trends analysis. (2016) - Teng, Minmin; Han, Chuanfeng; Lin, Xiaoqing
The traditional static evaluation model of environmental governance performance usually leads to large deviations in the results owing to the limitations of the approach itself. This paper demonstrates the unified expression of the static model, and furthermore, proposes the trend analysis evaluation model taking the effect of status, the effect of accumulation, the effect of the given trend, as well as the effect of trend change into consideration simultaneously. A case study of the 15 largest cities in China shows that the novel approach could balance the trade-off between the short-term and long-term efforts on environmental governance issues, and is overall more objective and effective.